2020
DOI: 10.1021/acs.jafc.0c04880
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evidence for RNA Adduction Resulting from Metabolic Activation of Methyleugenol

Abstract: Methyleugenol (ME) is a ubiquitous component in spices and other culinary herbal products. A prevailing theory in ME toxicity is its ability to be metabolically activated by P450 enzymes and sulfotransferases, which initiates sequential reactions of the resulting metabolites with functional biomolecules. The present study aimed at a potential interaction between the reactive metabolites of ME and RNA. Cultured mouse primary hepatocytes were incubated with ME followed by RNA extraction and NaOH and alkaline pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…At later time points, the adduct levels moderately decreased, which may be attributable to DNA repair. In line with this notion, a recent study provided evidence for the involvement of DNA repair in the removal of E-3′-N2-dG adducts, albeit with limited efficiency [105]. Another explanation for the decreased adduct levels found at later time points could be cytotoxicity, which is indeed observed at high estragole concentrations [104].…”
Section: Dose-response Studies On the Genotoxic Potential Of Estragol...mentioning
confidence: 73%
“…At later time points, the adduct levels moderately decreased, which may be attributable to DNA repair. In line with this notion, a recent study provided evidence for the involvement of DNA repair in the removal of E-3′-N2-dG adducts, albeit with limited efficiency [105]. Another explanation for the decreased adduct levels found at later time points could be cytotoxicity, which is indeed observed at high estragole concentrations [104].…”
Section: Dose-response Studies On the Genotoxic Potential Of Estragol...mentioning
confidence: 73%
“…Beside this, Yang et al recently showed that reactive metabolites of methyleugenol were also able to form RNA adducts [118]. However, the biological consequences of these RNA adductions are so far unclear, as also mentioned by the authors.…”
Section: Genotoxicity Of Methyleugenol Vs Elemicinmentioning
confidence: 87%
“…The spontaneous departure of sulfate anion results in the formation of the corresponding benzylic cations (S N 1 reaction). The resultant electrophilic species react with nucleophilic sites of biological macromolecules such as DNA, and the biomolecule adduction disturbs the corresponding biological functions, leading to genotoxicity. , 1′-Hydroxy metabolite of MYR (M5, Scheme ) was reported to be more cytotoxic than MYR itself . The reactive metabolites of methyleugenol and safrole interact covalently with RNA previously. , With reactive metabolites of MYR, we evaluated the risk of RNA adduction.…”
Section: Discussionmentioning
confidence: 99%